EVALUASI TINGKAT KESEHATAN BANK SYARIAH DENGAN INOVASI METODE KOMBINASI CAMELS DAN RGEC (STUDI PADA BANK NTB SYARIAH TAHUN 2018-2020) - Linda Mayasari1 Mayasari; Muhammad Hilmy Alfaruqi; Sudrajat Martadinata (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2022)
The growth of Islamic banking in Indonesia continues to increase every year. The increase can be seen from the growth of Third Party Funds (TPF), increasingly open market penetration, Islamic banking literacy has also expanded, and the total assets of both Sharia Commercial Banks (BUS) and Sharia Business Units (UUS) continue to grow every year Amidst growing inclusivity (openness) of the sharia banking industry, increasingly adding alternatives to the public to have banking services and products that are in accordance with social and economic preferences. It is very important for the Islamic banking industry to maintain operational soundness in accordance with regulatory provisions, in this case Bank Indonesia and the Financial Services Authority (OJK), in addition to balancing profitability and capable and evaluative lending. The bank soundness assessment method continues to develop, there are two methods used in this research, the first method is CAMELS (Capital-Assets quality Management-Earning-Liquidity-Sensitivity to market risk) in accordance with BI regulation No.6/10/PBI/2004. The second method is the RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital) method. This research is a type of descriptive research with a quantitative approach. The object of this research is the financial statements for three periods, namely 2018 to 2020. The data collection technique in this study is by reviewing the financial statements released by audits from public accountants and company records or documents. The research location is at Bank NTB Syariah. This study aims to determine the soundness of Bank NTB Syariah with the innovative combination method of CAMELS and RGEC.